2012
DOI: 10.1111/j.1582-4934.2011.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M decreases interleukin‐1 β secretion by human synovial fibroblasts and attenuates an acute inflammatory reaction in vivo

Abstract: Oncostatin M (OSM) is a pleiotropic cytokine of the IL-6 family and displays both pro-inflammatory and anti-inflammatory activities. We studied the impact of OSM on the gene activation profile of human synovial cells, which play a central role in the progression of inflammatory responses in joints. In synovial cells stimulated with lipopolysaccharide and recombinant human granulocyte-macrophage colony-stimulating factor, recombinant human OSM and native OSM secreted by human granulocytes both reduced the gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 70 publications
3
19
0
Order By: Relevance
“…For example, P38 Mapk plays a role in signal transduction within the normal inflammatory cascade and is only activated in PF and C animals (Cuadrado & Nebreda 2010). Moreover, Adamts12 modulates neutrophil apoptosis during inflammation, while Osm attenuates the inflammatory response (Moncado-Pazos et al, 2012; Dumas et al, 2012). Thus, inhibition of Adamts12 and activation of Osm in control animals may blunt their responses to adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…For example, P38 Mapk plays a role in signal transduction within the normal inflammatory cascade and is only activated in PF and C animals (Cuadrado & Nebreda 2010). Moreover, Adamts12 modulates neutrophil apoptosis during inflammation, while Osm attenuates the inflammatory response (Moncado-Pazos et al, 2012; Dumas et al, 2012). Thus, inhibition of Adamts12 and activation of Osm in control animals may blunt their responses to adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the clear evidences of its inflammatory activity, some studies show different aspects of OSM. Recent studies have reported that OSM decreases the production of inflammatory factors such as CXCL‐8 and IL‐1β in human SFs (Dumas et al, 2012). Taken together, the role of OSM should be further investigated in RA.…”
Section: Discussionmentioning
confidence: 99%
“…OSM is a potent mitogen for dermal fibroblasts and limits monocytic cell recruitment during inflammation via suppression of CCL5 . IL10 over expression is associated with reduced inflammatory mediators and promotion of regenerative healing while lower MMP3 levels are associated with impaired wound healing in mice and humans . Late up‐regulation of these genes was not observed in controls and this response may contribute to differences in observed outcomes.…”
Section: Discussionmentioning
confidence: 99%